Analysis of creatine kinase and alpha-actin concentrations in soccer pre-season - Pimenta, E.; Barbosa Coelho, D.; Capettini, L.; Gomes, T.; Pussieldi, G.; Ribeiro, J.; Gomes-Filho, A.; Silami-Garcia, E. (Revista Brasileira de Ciência e Movimento, 2015)
The purpose of the present study was to assess muscle overload through changes in creatine kinase (CK) activity and serum concentration of á-actin in soccer players in response of two months of pre-season physical training. Basic procedures: Ten professional athletes (26 ± 6 years of age) undergoing arduous training were evaluated. Serum CK activity and á-actin serum concentration were determined at the beginning and end of two months of pre-season training. Effort intensity was determined throughout the training sessions by monitoring heart rate (HR). Serum CK activity was determined using the colorimetric method. Plasma á-actin concentration was evaluated using ELISA and confirmed using the Western Blot method. Main Findings: Serum CK activity and á-actin concentration were higher in the post-training period in comparison to the pre-training period (CK: PRE 65.5 ± 4.2 U/L, POST 435.7 ± 70.0 U/L, p=0.0004; á-actin by Western Blot: PRE 42.9 ± 21.6 ìg/mL, POST 68.1 ± 19.1 ìg/mL, p=0.0004; by ELISA: PRE 70.63 ± 10.4 ìg/mL, POST 101.80 ± 17.3 ìg/mL, p=0.0125). Conclusions: The significant increases in á-actin concentration and in CK activity of soccer players over the two-month pre-season indicated that an elevated training overload was imposed upon the athletes.